Weakly nonlocal Rayleigh waves in orthotropic half-spaces coated by an orthotropic layer with sliding contact - Vinh, Pham Chi; Anh, Vu Thi Ngoc; Nga, Nguyen Thi (Vietnam Journal of Mechanics, 2025)
In this paper, we study the propagation of Rayleigh waves in nonlocal orthotropic half-spaces coated by a nonlocal orthotropic layer with sliding contact using the weakly nonlocal elasticity model. This model was recently introduced and different from other existing nonlocal models it has been proven to be well-posed for all harmonic plane wave problems. The transfer matrix method and the effective boundary condition method are employed for deriving the explicit dispersion equation of Rayleigh waves. Using the obtained dispersion equation, the effect of the nonlocality and the thickness of the layer on the velocity of Rayleigh waves is considered through some numerical examples. It is shown that the nonlocality and the thickness of the layer strongly affect the velocity of Rayleigh waves and they make it decreasing. Since the dispersion equation of Rayleigh waves is totally explicit, it will be a powerful tool for monitoring the health of the layer/half-space structures during loading.